THE IMPACT OF ATTITUDES ON THE INTENTION TO USE ARTIFICIAL INTELLIGENCE TECHNOLOGY IN HEALTHCARE SERVICES - Maria Arifani; Yoke Pribadi; Angela Caroline; Triningtyas Elisabeth Putri Gusti; Agus Gunawan (Jurnal Administrasi Bisnis, 2024)
This study explores how Artificial Intelligence (AI) is being adopted in workplace settings, with a focus on the healthcare sector. Guided by the Theory of Planned Behavior (TPB) and Theory of Reasoned Action (TRA), the research examines factors that shape employees' willingness to continue using AI. Insights from 112 survey respondents from across various sectors in Indonesia especially in health sector, measuring General Attitude towards AI (GAAIS) and Continuance Intention (CI) give results that indicate a positive attitude towards AI significantly affects employees’ intention to continue using AI, with perceived support and skills enhancing acceptance. Interviews with healthcare professionals reveal that positive attitudes, trust in AI, and support from peers significantly influence adoption. However, concerns about data privacy and algorithmic fairness remain key challenges. While AI demonstrates its potential to improve efficiency in both routine and complex tasks, successful integration requires human supervision and tailored training. Conclusively, companies are recommended to foster a supportive environment and provide training to reduce resistance and enhance AI integration for productivity and efficiency. By enhancing transparency, strengthening data protection, and fostering a supportive environment, organizations can ensure AI becomes a trusted partner in driving productivity and innovation.